2015
DOI: 10.1556/achrom.27.2015.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Determination of nicotine and three minor alkaloids in tobacco by hydrophilic interaction chromatography-tandem mass spectrometry

Abstract: Summary.A reliable, sensitive and rapid method for determination of nicotine and three minor alkaloids (cotinine, anabasine and nornicotine) in tobacco by ultra-high performance liquid chromatography in hydrophilic interaction chromatography mode coupled with tandem mass spectrometry (HILIC-MS/MS) has been established. HILIC separation was performed on a BEH HILIC column using isocratic elution at 0.5 mL/min with acetonitrile:water (85:15, v/v) mobile phase containing 5 mmol/L ammonium acetate (pH 5.00). Separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…The nornicotine and anabasine in cigarette smoke likely possess abuse potential . The contents of nicotine, anabasine, and cotinine have been widely studied in tobacco leaves, tobacco fillers, etc. Their metabolites in human urine, plasma and saliva samples have been used as biomarkers for the study of tobacco use.…”
Section: Resultsmentioning
confidence: 99%
“…The nornicotine and anabasine in cigarette smoke likely possess abuse potential . The contents of nicotine, anabasine, and cotinine have been widely studied in tobacco leaves, tobacco fillers, etc. Their metabolites in human urine, plasma and saliva samples have been used as biomarkers for the study of tobacco use.…”
Section: Resultsmentioning
confidence: 99%
“…Minor tobacco alkaloids are naturally occurring compounds [5] that are structurally [6] and functionally [7][8][9] analogous to nicotine, the primary psychoactive component in cigarettes, and have been the subject of research on novel therapeutics for smoking cessation [10], cognitive disorders including Alzheimer's disease [11][12][13] and Parkinson's disease [14], traumatic brain injury [15], inflammatory bowel disease [16] and psoriasis (Rock Creek Pharmaceuticals), as well as a novel strategy for pain management [17]. Previous research investigating the role of nicotine on body weight has repeatedly demonstrated that cigarette smoking and/or nicotine administration produces sustained weight loss and reduced food intake [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Since nicotine is synthesized in the roots and transported to the leaves, its concentration influences the plant development. [8,9] Therefore, the nicotine content evaluation is an important parameter for the tobacco quality in cigarettes [10]. For cigarettes with intentionally reduced amounts of nicotine, it is necessary for the plants to be genetically modified; it takes 8-12 years of research for a certain variety to be commercialized [8,11].…”
Section: Introductionmentioning
confidence: 99%